2022
DOI: 10.1111/apps.12420
|View full text |Cite
|
Sign up to set email alerts
|

The hidden performance costs of professional isolation? A latent change score model of professional isolation during the early stage of COVID‐19 pandemic

Abstract: Although past research has found that professional isolation can affect discernible work‐related outcomes (e.g. job performance and turnover) and important job attitudes, researchers have not examined its impact on those less discernible but still costly work behaviours. Drawing on self‐regulation theories, this study examined the effect of professional isolation on employees' cyberloafing and time theft through self‐control capacity impairment. With longitudinal data collected from 343 U.S. employees across f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Specifically, workplace ostracism implies an omission of act (i.e., absence of attention) whereas other forms of mistreatment involve the commission of acts (i.e., negative attention) (Ferris et al, 2017). As such, workplace ostracism is distinct from other constructs such as professional isolation, which refers to employees' beliefs that they are disconnected from others at work due to practical constraints (e.g., remote working) (Peng et al, 2023).…”
Section: Workplace Ostracismmentioning
confidence: 99%
“…Specifically, workplace ostracism implies an omission of act (i.e., absence of attention) whereas other forms of mistreatment involve the commission of acts (i.e., negative attention) (Ferris et al, 2017). As such, workplace ostracism is distinct from other constructs such as professional isolation, which refers to employees' beliefs that they are disconnected from others at work due to practical constraints (e.g., remote working) (Peng et al, 2023).…”
Section: Workplace Ostracismmentioning
confidence: 99%
“…Furthermore, Mwape, et al 45 and Pimmer, et al 44 , suggested that participants with advanced knowledge and skills exhibited fewer feelings of professional isolation compared to their counter parts. Most importantly, the trajectory of professional isolation may be improved or changed less dramatically by encouraging employees to share knowledge, skills, experiences, and their professional challenges 46 .…”
Section: Discussionmentioning
confidence: 99%